Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Cavanagh, Rachel D.; Melbourne-Thomas, Jess; Grant, Susie M.; Barnes, David K. A.; Hughes, Kevin A.; Halfter, Svenja; Meredith, Michael P.; Murphy, Eugene J.; Trebilco, Rowan; Hill, Simeon L. (Frontiers in Marine Science, 2021)
The Southern Ocean supports ecosystem services that are important on a global scale. Climate change and human activities (tourism, fishing, and research activities) will affect both the demand for, and the provision of, these services into the future. Here we synthesize recent assessments of the current status and expected future climate-driven changes in Southern Ocean ecosystems and evaluate the potential consequences of these changes for the provision of ecosystem services. We explore in detail three key services (the Antarctic krill fishery, the ‘blue carbon’ pathway, and Antarctic tourism), tracing the consequences of climate change from physical drivers through biological impacts to the benefits to humans. We consider potential non-climatic drivers of change, current and future demands for the services, and the main global and regional policy frameworks that could be used to manage risks to the provision of these services in a changing climate. We also develop a formal representation of the network of interactions between the suite of potential drivers and the suite of services, providing a framework to capture the complexity of this network and its embedded feedback loops. Increased consideration of the linkages and feedbacks between drivers and ecosystem services will be required to underpin robust management responses into the future.